2019
DOI: 10.48550/arxiv.1909.04222
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Covariance Matrix Estimation under Total Positivity for Portfolio Selection

Abstract: Selecting the optimal Markowitz porfolio depends on estimating the covariance matrix of the returns of N assets from T periods of historical data. Problematically, N is typically of the same order as T , which makes the sample covariance matrix estimator perform poorly, both empirically and theoretically. While various other general purpose covariance matrix estimators have been introduced in the financial economics and statistics literature for dealing with the high dimensionality of this problem, we here pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Observe that h i,j ( δi,j ) is a continuous function of δi,j as a consequence of the bounded convergence theorem. Hence, the intermediate value theorem allows us to conclude (6.4.3) if we can show that h i,j (δ) ≤ H and h i,j (C 3 δ) ≥ H. The first inequality h i,j (δ) ≤ H follows from the fact that exp z 1 z 2 + δi,j g i,j (z) − exp(z 1 z 2 ) ≤ exp 1 + δi,j g i,j (z) − exp (1) and changing the limits of the integral. The second inequality h i,j (C 3 δ) ≥ H follows from the following estimates.…”
Section: Differential Characterization and Setupmentioning
confidence: 96%
See 2 more Smart Citations
“…Observe that h i,j ( δi,j ) is a continuous function of δi,j as a consequence of the bounded convergence theorem. Hence, the intermediate value theorem allows us to conclude (6.4.3) if we can show that h i,j (δ) ≤ H and h i,j (C 3 δ) ≥ H. The first inequality h i,j (δ) ≤ H follows from the fact that exp z 1 z 2 + δi,j g i,j (z) − exp(z 1 z 2 ) ≤ exp 1 + δi,j g i,j (z) − exp (1) and changing the limits of the integral. The second inequality h i,j (C 3 δ) ≥ H follows from the following estimates.…”
Section: Differential Characterization and Setupmentioning
confidence: 96%
“…Smooth MTP 2 distributions have long been studied in the literature. Examples include, but are not limited to, (1) pairwise marginals of Gaussian latent tree models [13], such as Brownian motion tree models and 1 factor analysis models, (2) joint distributions of pairs of time points of a strong Markov process on the real line with continuous paths [23], such as a diffusion process, and (3) MTP 2 transelliptical distributions, such as MTP 2 multivariate t-distributions, which are commonly used in finance [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the precision matrix having nonpositive off-diagonal entries Θ * jk is equivalent to nonnegative partial correlations −Θ * jk / Θ * jj Θ * kk (Bølviken, 1982). Examples of practical covariance estimation problems with nonnegative partial correlations abound (see, e.g., Lake and Tenenbaum, 2010;Slawski and Hein, 2015;Agrawal, Roy and Uhler, 2019). More generally, Karlin and Rinott (1983) showed that for the normal distribution the condition that the precision matrix belongs to M p×p is equivalent to multivariate total positivity of order two (MTP 2 ).…”
Section: Introductionmentioning
confidence: 99%